2020
DOI: 10.1097/qai.0000000000002445
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Pregnancies Among US Women Living With HIV in the SMARTT Study: Temporal Changes in HIV Disease Status and Predictors of Preterm Birth

Abstract: BACKGROUND-Birth rates among women living with HIV (WLHIV) have increased recently, with many experiencing multiple pregnancies. Yet, viral suppression is often not sustained between pregnancies. Additionally, protease inhibitors (PIs) have been associated with preterm birth, but associations between integrase strand transfer inhibitors (INSTIs) and preterm birth are less well characterized.METHODS-We studied WLHIV with ≥2 liveborn infants enrolled into the Pediatric HIV/AIDS Cohort Study (PHACS) Surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Other studies have identified an association between INSTI exposure during pregnancy and preterm birth. [18] Of note, our comparison group included women who received PIs, which are associated with increased rates of preterm birth [35,36]; this may have limited our ability to detect an association between INSTI exposure and preterm birth, should one exist. We noted that women on INSTI had fewer grade ≥3 chemistry and hematology laboratory abnormalities compared to women on non-INSTI regimens, although this could not be compared in a formal statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have identified an association between INSTI exposure during pregnancy and preterm birth. [18] Of note, our comparison group included women who received PIs, which are associated with increased rates of preterm birth [35,36]; this may have limited our ability to detect an association between INSTI exposure and preterm birth, should one exist. We noted that women on INSTI had fewer grade ≥3 chemistry and hematology laboratory abnormalities compared to women on non-INSTI regimens, although this could not be compared in a formal statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified an association between INSTI exposure during pregnancy and preterm birth. [18] Of note, our comparison group included women who received PIs, which are associated with increased rates of preterm birth [35, 36]; this may have limited our ability to detect an association between INSTI exposure and preterm birth, should one exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations